Ameloblastic fibroma in an alpine chamois (Rupicapra rupicapra). (April 2015) - Scaglione, F.E.; Iussich, S.; Grande, D.; Carpignano, M.; Chiappino, L.; Sereno, A.; Ferroglio, E.; Bollo, E.
Highlights: This is the first report of an ameloblastic fibroma in a wild ungulate. Spontaneous odontogenic tumors are rare in humans and in animals. Histological and immunohistochemical examinations are essential for the diagnosis. Abstract: Spontaneous odontogenic tumors are neoplasms characterized by a mixed odontogenic ectomesenchymal and odontogenic epithelial origin; they are rare in both humans and animals. A 3-year-old male Alpine Chamois ( Rupicapra rupicapra ) was found dead in north-west Italy, and was referred for the necropsy to the Department of Veterinary Sciences of the University of Turin (Italy). At the external examination a 10 × 8 cm, exophytic, red-pink, smooth, firm and ulcerated mass was observed on the inferior lip. Histologically the tumor was characterized by spindle shaped cells arranged in bundles in an abundant hyaline matrix. Multifocal and rare chords of odontogenic epithelium mixed with rare melanocytes that penetrate the neoplasia were visible. Immunohistochemistry showed a clear cytokeratin positivity of epithelial clusters. Macroscopical, histological and immunohistochemical findings were consistent with a diagnosis of locally infiltrative ameloblastic fibroma. To our best knowledge, this is the first report of this tumor in a wild ungulate and in Alpine Chamois.